Morality In Oscar Wilde's The Picture Of Dorian Gray'. A Sociological Approach - Yuniwati, Ika Muslikhah (2004)
This study, the writer analyzes The Picture of Dorian Gray written by Oscar Wilde by using sociological approach. This novel describes how the society influences moral personality in the late nineteenth century that reflects in Revolution Industry. The study belongs to qualitative method. In this method, the writer uses two data sources, namely primary and secondary data sources. The primary data sources and the object of the study are the novel The Picture of Dorian Gray itself, meanwhile the secondary data is any literature related with this study. The writer collects the data from both primary and secondary data that relating with this study. Then, the technique of data analysis is a descriptive analysis and content analysis. To prove that The Picture of Dorian Gray is based on the social background of English in the late nineteenth century, the study uses a Sociological Approach in analysis. Based on the analysis, the writer conclude that the novel is a literary work, which has close relation with the background of the society at the late of nineteenth century, especially in Victorian period. Oscar Wilde reflects the social condition in his literary work. The sociological analysis shows that the moral value influences by society.